522 Audit of Acute Lower Gastrointestinal Bleed Management in a District General Hospital. (4th May 2021) - Mallick, S; Salem, R; Payne, A
Abstract: Introduction: Acute Lower Gastrointestinal Bleed (ALGIB) is a common emergency surgical referral. This project aims to audit current practice at a district general hospital against new British Society of Gastroenterology guidelines, which gives recommendations regarding assessment (Oakland score), investigation and management. Method: A retrospective study was undertaken over one year (2019) of patients presenting to A&E or referred via GP with ALGIB. Patients were identified through the coding department. An online proforma was used for data collection, which was analysed with SPSS. Results: 76 appropriate patients identified. Median length of hospital stay was 1 day. 10 patients (13.2%) scored ≤8 (probability of safe discharge 95%), 19 (11.8%) patients scored ≤9 (probability of safe discharge 93%) and 57 patients (75%) scored ≥10. 19 patients discharged the same day, of which 3 (15.8%) scored ≤8 and 8 (42.1%) scored ≤9. 23 patients admitted overnight, of which 5 (21.7%) scored ≤8 and 6 (26.1%) scored ≤9. Of 66 patients classified as 'major', 41 (62.1%) did not have a colonoscopy. Conclusions: Introduction of a scoring mechanism and disseminating guidelines will enable GPs and A&E doctors to safely discharge ALGIB patients with appropriate outpatient investigations and reduce surgical admissions. There is currently poor compliance with inpatient investigations.